Analysis of the Legal Status of Joint Office in Notary Civil Partnership: Perspective of Article 20 of UUJN-P - Annisa, Yusifa Nur; Dewantara, Reka; Jauharoh, Arini (IJBLE Scientific Publications Community Inc., 2024)
This article focuses on the Analysis of the Legal Status of Joint Offices in Notary Civil Partnerships: Perspective of Article 20 of the Law Concerning Notary Positions (from now on UUJN-P), which focuses on the legal status of joint offices by notary civil partnerships. The research in this article uses normative juridical research. Aims to describe and analyze the legal status of establishing a joint office by a civil partnership of notaries. Notaries can enter into civil partnerships to form a joint office as regulated in Article 20 of Law Number 02 of 2014 concerning Amendments to Law Number 30 concerning Notary Positions. Establishing a joint office can be convenient for notaries when opening a notary office, which requires expensive costs. However, there is legal ambiguity regarding the regulation of the legal status of the establishment of a joint office by a notary civil association, where there is a synonym for terms in article 20 UUJN, which equates notary civil partnerships with notary joint offices and civil partnerships in the Civil Code.